2023
DOI: 10.3390/app13106152
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cartilage Conduction Hearing Devices Designed by Ear Impression and Computed Tomography

Abstract: The ear molds and shells of hearing devices are generally designed using ear impressions. Computed tomography (CT) can provide information concerning ear structure, which can be utilized in computer-aided design to create hearing devices. This study aimed to compare the differences in hearing devices designed using either ear impressions or CT images. The ear chip of a cartilage conduction (CC) hearing device was designed based on the ear impression and CT images of patients with aural atresia. Three patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The mechanical impedance is described in level notation (ref. 1 Ns/m) as in a study by Flottorp et al [13], in which the mechanical impedance of the mastoid and forehead was measured. The variability of the measured mechanical impedance was small, below about 2000 Hz, but significantly above about 2000 Hz.…”
Section: Mechanical Impedance Of Ear Cartilagementioning
confidence: 99%
See 2 more Smart Citations
“…The mechanical impedance is described in level notation (ref. 1 Ns/m) as in a study by Flottorp et al [13], in which the mechanical impedance of the mastoid and forehead was measured. The variability of the measured mechanical impedance was small, below about 2000 Hz, but significantly above about 2000 Hz.…”
Section: Mechanical Impedance Of Ear Cartilagementioning
confidence: 99%
“…CCHAs have been developed for patients suffering from external auditory canal atresia and have demonstrated effectiveness and advantages in clinical studies [5][6][7]. In Japan, the product has been commercially available since 2017 and several medical institutions have published various reports on it [8][9][10][11][12][13]. Furthermore, in recent years, the applicability of CCHAs to patients diagnosed with various hearing impairments has also been under consideration [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ear chips are custom fitted, made based on ear impressions. Instead of taking an impression of the ear, computed tomography (CT) images can also be utilized for designing the vibrator [ 20 ]. Compared to the conventional process, the merits of the design using CT images are as follows: no risks related to taking the ear impression, advantage of understanding the shape of the ear in 3D, no physical transport or shipment of an ear impression, and CT images can be sent instantly via the internet.…”
Section: Performance Of CC Hearing Aidsmentioning
confidence: 99%
“…If a CT scan is performed for diagnosis or other purposes, the images can be used without additional risk. A previous study reported that the performance of a CT-based vibrator is not significantly inferior to that of an impression-based vibrator [ 20 ]. In contrast, the simple type is available for all ear conditions and can be prepared in advance; patients can try it quickly and unnecessary ear chip costs are also reduced.…”
Section: Performance Of CC Hearing Aidsmentioning
confidence: 99%